Letter - Schevenels, Walther, b. 1894
001-0135-001 INTERNATIONAL FEDERATION OF TRADE UNIONS From MR.SCHEVENELS To MR.BELL Date 3rd November Ref .No 4685 Dear Ernie, I just got information that the Spanish Group in Mexico, leadership Belarmino Tomas, Vidal Rossell, changed its address from Balderas 37 to Tacuba 15, also Mexico, D.F. Yours cordially, Schevenels 292/946/1/135